Langerhans cell histiocytosis forming an asymptomatic solitary nodule in the spleen. - Lam, K Y (1996)
A case of solitary Langerhans cell histiocytosis (LCH) in the spleen of a 29 year old Chinese man, discovered incidentally at necropsy, is reported. This is the first documented case of LCH confined to the spleen and suggests that LCH should be included in the differential diagnosis of space occupying lesions in the spleen.